Analysis of the Carrying Capacity of Nabita Tourism at Nagari Binjai Tapan, Ranah Ampek Hulu District, Tapan, Pesisir Selatan District - Filza Nadilla Utari; Rika Despica; Nefilinda (PT FORMOSA CENDEKIA GLOBAL, 2023)
The aim of the study was to analyze the carrying capacity of the Nabita tourist attraction in Nagari Binjai Tapan, Ranah Ampek Hulu Tapan District, and Pesisir Selatan District. There are 3 formulations of the problem, namely: the carrying capacity of the Nabita tourist attraction, the management support, and the attractiveness of the Nabita tourist attraction. The research method is descriptive quantitative. Research results: 1). The carrying capacity of the Nabita tourist area, as a whole the Nabita Tourism Object can have a carrying capacity of 231 people/day, 2). Management carrying capacity obtained a percentage of 100% so it can be concluded that what is needed to manage the Nabita tourist attraction, 3). The attractiveness of the Nabita tourist attraction was obtained with a total number of 10,501, an average of 3.961, a percentage of 79.22 with very attractive criteria.